An analysis of multiple choice questions (MCQs): Item and test statistics from mathematics assessments in senior high school - Kusumawati, Mutiara; Hadi, Samsul (REID (Research and Evaluation in Education), 2018)
The multiple-choice test is a common test format used in education. One of the purposes of this test is to evaluate the success of the learning process in a particular subject. Therefore, the efficiency of the evaluation depends on the quality of the test items used. This research was conducted in order to reveal the quality of the final mathematics examination items statistically. It was descriptive quantitative research employing two-parameter logistic (2pl) model of Item Response Theory (IRT). The data were obtained from the sample of 353 students established using the purposive sampling technique. This finding shows that 40% of the 35 items tested are very difficult, 60% are in the medium level, and there is no easy item. The most difficult material is the trigonometric calculation. The percentage of the item discrimination index is described as follows: 8.57% of the items are categorized as very low, 51.43% are categorized as low, 31.43% of the items have a medium item discrimination index value, 5.71% have a high item discrimination index value, and 2.86% of the items are categorized as very high. Moreover, the research found that all distractors functioned well. The highest information on ability Î¸ = 0.4 with information function value of 5.38 and SEM = 0.6. This test is suitable for students with the ability of -1.42 <Î¸ <2.65.